Relasi Manusia dan Alam dalam al-Qur’an: Studi Komparatif Tafsir Al-Azhar dan Tafsir Al-Mishbah - Muhammad Fajar Ali (Prodi Ilmu al-Qur'an dan Tafsir, 2025)
This study examines the interpretation of the verses of the Qur'an concerning the relationship between humans and nature through a comparative study between Tafsir Al-Azhar by Buya Hamka and Tafsir Al-Mishbah by M. Quraish Shihab. The analysis uses Talcott Parsons' functionalism theory with the AGIL (Adaptation, Goal Attainment, Integration, and Latency) approach. This article examines how the two commentators interpret the verses relating to the relationship between humans and nature and their relevance in the Indonesian context. The method used is qualitative descriptive with a comparative approach. The results of the study show that both commentators have similarities in emphasizing the importance of harmony between humans and nature as a form of devotion to Allah SWT. However, their approaches are different: Buya Hamka is more spiritual and moralistic, while Quraish Shihab is more analytical and contextual. The relationship between humans and nature is emphasized as a harmonious relationship that emphasizes responsibility, sustainability, and spiritual awareness. In the Indonesian context, both view humans as caliphs who are responsible for maintaining the sustainability of nature. The relevance of this interpretation is very important in the context of Indonesia which is rich in the diversity of natural resources. especially in building ecological awareness based on Islamic values. both thoughts provide theological and practical solutions to the modern ecological crisis. And maintain moral awareness by making religion and spirituality as guidelines for preserving nature. With the AGIL approach, these two interpretations provide a theological and practical basis for facing modern challenges without forgetting spiritual and cultural values.